Inclusão de catadores de materiais recicláveis: análise fundamentada na teoria ator-rede - Ribeiro, Priscila Soraia da Conceição (2022)
Collectors of recyclable materials play an important role in the waste recovery process through the reuse of discarded materials that can be reintroduced into the production chain. The complexity of converting political options into socially, economically, and environmentally acceptable strategies places collectors of recyclable materials and the challenges they experience on the agendas of research in science, technology, and society. This study aims to search for elements that contribute to interpret the presence of pickers in the solid waste management at regional scale through the analysis of planning instruments and, at municipal scale, from the perspective of the complex relationship between human and non-human actors involved. It was decided to carry out a discussion based on an empirical study applied to the Sorocaba and Médio Tietê Rivers Watershed Committee and the municipality of Porto Feliz. The Grounded Theory is the methodology adopted in data collection and analysis, which enabled the necessary research restructuring in the face of the immense crisis brought about by the pandemic. This method encourages the expansion of knowledge in the area through the connection of theoretical concepts and significant aspects of the actors’ experiences. The techniques applied for data collection included analyses of regulatory instruments and integrated solid waste management plans of municipalities that constitute the watershed under study, semi-structured interviews held with key actors in the planning and execution of the waste collection in the municipality of Porto Feliz, participant observation, and informal interviews. The results are analyzed from concepts derived from the Actor-Network Theory. The regional analysis revealed the importance of the guidelines of municipal plans for achieving universalization goals; however, due to the content they cover, they are unable to translate the interests of Federal Law 12.305/2010 regarding the inclusion of waste pickers. Thus, it could be concluded that the adoption of more efficient strategies for long-distance control is essential, aligning the interests of Federal and Municipal Governments. Ats municipal scale, it was possible to observe the efforts undertaken by multiple actors, sometimes in the construction and sometimes in the destabilization of a support network for the establishment of a labor cooperative. The network suffered dissidents and was destabilized by the influence of the original network and by unexpected events, which made the results achieved opposite to desired ones. In conclusion, the network was not stabilized, and the municipal solid waste management remained unchanged.